A critique of the literature on past convictions and the probability of guilt. (18th May 2022) - Hunt, Ian
Abstract: This article is a critical review of the growing literature that applies probability analysis to past convictions, in the context of determining guilt in criminal trials. Recent arguments for potentially relaxing rules that exclude past conviction evidence are sustained, but particular flaws and limitations in the theses from Hamer (2019, The significant probative value of tendency evidence. Melbourne University Law Review 42, 506–550) and Redmayne (2015, Character in the criminal trial . Oxford University Press) are exposed. Much of the critique of Redmayne (2015) made by Robinson (2020, Incorporating implicit knowledge into the Bayesian model of prior conviction evidence: some reality checks for the theory of comparative propensity. Law, Probability and Risk 19, 119–137) is dismissed. We should aim to foster a continued lively debate in the literature, gather more data, and narrow the distance between those arguing about theoretical probability analysis and those focused on actual courtroom usage of past conviction evidence.